The Role of Spirituality in Management Education - Keefner, Jenna; Kučera, Dušan; Viktora, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Spirituality, distinct from religion, is framed in the scope of this paper as a search for meaning, connection, and ethical grounding in the context of educational leadership and management. By synthesizing insights from anthropology, psychology, and management theory, the study investigates the potential of spiritual principles intersecting with leadership practices, emotional intelligence, and organizational ethics.
Vedoucí práce: Dušan Kučera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses